2007
DOI: 10.1073/pnas.0703934104
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of action for a human ether-a-go-go-related gene 1 potassium channel activator

Abstract: Activation of human ether-a-go-go-related gene 1 (hERG1) K ؉ channels mediates cardiac action potential repolarization. Drugs that activate hERG1 channels represent a mechanism-based approach for the treatment of long QT syndrome, a disorder of cardiac repolarization associated with ventricular arrhythmia and sudden death. Here, we characterize the mechanisms of action and the molecular determinants for binding of RPR260243 [(3R,4R)-4-[3-(6-methoxy-quinolin-4-yl)-3-oxo-propyl]-1-[3-(2,3,5-trifluorophenyl)-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
133
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(140 citation statements)
references
References 42 publications
6
133
1
Order By: Relevance
“…All known hERG1 channel agonists either slow the onset and/or shift the voltage dependence of inactivation to more depolarized potentials (8)(9)(10). The effects on other channel gating properties such as the voltage dependence of activation and rate of channel deactivation are variable and drug specific.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All known hERG1 channel agonists either slow the onset and/or shift the voltage dependence of inactivation to more depolarized potentials (8)(9)(10). The effects on other channel gating properties such as the voltage dependence of activation and rate of channel deactivation are variable and drug specific.…”
mentioning
confidence: 99%
“…carboxylic acid] (6), defined here as a ''type 1'' hERG1 agonist, binds to a receptor site located at the intracellular ends of the S5 and S6 segments of a single hERG1 subunit to cause a profound slowing of deactivation rate and a positive shift in the voltage dependence of pore (P)-type inactivation gating (9). P-type inactivation of hERG1 is very rapid, and similar to C-type inactivation of other voltage-gated K ϩ (Kv) channels, is believed to be caused by a subtle structural change in the selectivity filter (SF) of the outer pore domain (11).…”
mentioning
confidence: 99%
“…However, the exact molecular determinants of hERG activator function remain unresolved, with most of the knowledge about possible binding sites derived from mutagenesis experiments. Sangunetii et al found that two groups of residues have different effects on RPR260243 [24,37] . One group, including L553, F557 (S5), and N658, V659 (S6), affects the inactivation and deactivation effect of RPR260243 on the hERG channel, while mutations in the other group of residues, including V549, L550 (S4-S5 linker), and I662, L666, Y667 (intracellular S6 segment), only hinder the transition to the closed state of the channel.…”
Section: Binding Site Of Small-molecule Herg Activatorsmentioning
confidence: 99%
“…However, due to the limitations of existing high throughput screening methods and difficulties in assaying the channel on a large scale, few activators have been reported. Most of the existing activators originated from combinatorial chemistry libraries, including RPR260243 [22][23][24] , PD-118057 [25] , PD-307243 [26] , NS1643 [27] , NS3623 [28] , A-935142 [29] , ICA-105574 [30] , and KB130015 [31] . Addi-www.nature.com/aps Zhou PZ et al Acta Pharmacologica Sinica npg tionally, a natural product, mallotoxin, has also been shown to activate hERG [32] .…”
Section: Herg Activatorsmentioning
confidence: 99%
See 1 more Smart Citation